2016
DOI: 10.1111/ijac.12569
|View full text |Cite
|
Sign up to set email alerts
|

High‐temperature Bending Strength of Self‐Healing Ni/Al2O3 Nanocomposites

Abstract: Bending strength of 5 vol.% Ni/Al2O3 composites as a function of testing temperature is investigated at temperatures ranging from room temperature to 1200°C. Self‐healing performance at high temperatures of the composites is evaluated by conducting high‐temperature bending tests for as‐sintered, as‐cracked, and as‐healed specimens. Bending strength of as‐sintered specimens dramatically decreases from 995 MPa at room temperature to 205 MPa at 1200°C. Additionally, the plastic deformation of the as‐sintered spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…The interface energy between SiC and Al 2 O 3 matrix is higher than the transgranular fracture energy that causes their fracture obeys the transgranular fracture mechanism. 32) Figure 9 shows the fraction of surface crack disappearance as a function of heat-treatment temperatures for 5Ni/mullite with the previously reported results on 5Ni/(10ZrO 2 + Al 2 O 3 ), 33) 5Ni/Al 2 O 3 , 34) and 5Co/Al 2 O 3 . 19) The Ni/mullite requires a lower heat-treatment temperature for surface crack-disappearance than the others nanocomposites based on Al 2 O 3 matrix.…”
Section: Mechanical Propertiessupporting
confidence: 69%
See 2 more Smart Citations
“…The interface energy between SiC and Al 2 O 3 matrix is higher than the transgranular fracture energy that causes their fracture obeys the transgranular fracture mechanism. 32) Figure 9 shows the fraction of surface crack disappearance as a function of heat-treatment temperatures for 5Ni/mullite with the previously reported results on 5Ni/(10ZrO 2 + Al 2 O 3 ), 33) 5Ni/Al 2 O 3 , 34) and 5Co/Al 2 O 3 . 19) The Ni/mullite requires a lower heat-treatment temperature for surface crack-disappearance than the others nanocomposites based on Al 2 O 3 matrix.…”
Section: Mechanical Propertiessupporting
confidence: 69%
“…In other words, self-healing performance in Ni/Al 2 O 3 system is greater than that of SiC/Al 2 O 3 . However, applications of Al 2 O 3 at high temperatures would be concerned on their bending strength 26) and creep properties. 27) Lessing et al reported the creep rate at 1450 C of dense mullite was approximately one order of magnitude less than that of monolithic Al 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cracks are easily introduced into brittle ceramics during subsequent machining processes and operations, resulting in dramatically degraded mechanical strength 1 . In order to eliminate these surface cracks, it is of great importance to improve fracture toughness to enhance crack resistance.…”
Section: Introductionmentioning
confidence: 99%
“…However, they are brittle by nature and, thus, surface cracks and/or defects are easily introduced during machining processes or when ceramics are used as structural components in practical applications. When cracks appear in a ceramic material, its fracture strength and reliability are considerably reduced because such cracks act as fracture initiation sites when stress is exerted at the crack edges. Introducing self‐healing‐ability into ceramic has been an effective approach to eliminate existing surface cracks and recover lost mechanical strength and reliability.…”
Section: Introductionmentioning
confidence: 99%